Analysis of the dynamics of the nomenclature of medicines in the government program «Available medicines» - І. А. Кostiuk; J. V. Pelykh (The State Expert Center of the Ministry of Health of Ukraine, 2022)
The availability of medicines the public is a problem with the most acute health care systems. Not only the issue of physical availability of medicines, their availability in pharmacies, but also the economic assistance of the population to purchase drugs is relevant. To overcome these problems, the Government has recognized the introduction of a reimbursement process in the pharmaceutical sector. The content of improving the quality and life expectancy of the population, with increasing physical and economic accessibility of drugs for the treatment of the most socially significant diseases, April 1, 2017 the Government introduced a reimbursement program «Available medicines». In the beginning there were spreads with cardiovascular disease, type II diabetes and bronchial asthma. From October 1, 2021, the program includes drugs for the treatment of diabetes mellitus, mental and behavioral disorders, epilepsy. The aim of the work is to study the dynamics of the range of drugs included in the government programs «Available medicines» for 2017-2022. The content analysis of 13 issues of Registers of medicines subject to reimbursement shows the updating and growth of the number of international non-proprietary names and in accordance with the trade names of drugs for the treatment of nosologies, which countries have recognized as the best. The nomenclature of medicines has been updated twice with international non-proprietary names and in almost 3 varieties - by trade names compared to the first issue, which is associated with both the expansion of names for the treatment of the disease, which were in programs since 2017 and the emergence of new nosology from 2021. On average, the share of drugs of domestic pharmaceutical companies is only 60%, which opens a significant prospect of import substitution, reduces drug prices under the government program «Available medicines» and, for example, increase the physical and economic availability of drugs. The conducted studies allow us to conclude that there is a need to improve the assortment policy of the government program «Available medicines» using the population of Ukraine available drugs in accordance with the needs of the population and the standards for the treatment socially significant diseases.